The role of physical function and physical activity on cognitive function in the elderly - Chengyan Qi; Xianyun Wang; Dajun Li; Huini Ding; Jing Shen; Yuning Jiao; Wangziyan Lu; Yuandi Xi (Global Transitions)
The aim of this study is to clarify the role of physical activity level and physical function on cognitive function of the elderly. A nested case–control investigation from a middle-aged and elderly cognitive health cohort was conducted. 103 mild cognitive impairment (MCI) patients were selected for the purpose of the study and matched 1:1 according to age and sex. Handgrip strength, gait speed and 5-time chair stand test were used to evaluate physical function. The physical activity scale for the elderly (PASE) was used to assess physical activity level. The Montreal cognitive assessment (MoCA) was used to quickly screen the mild cognitive impairment of the subjects. Body composition was estimated by bioelectrical impedance analysis. The total score of MoCA and the scores of different cognitive domains in two groups were different, handgrip strength was lower in the MCI group. Multivariate logistic regression model results showed that handgrip strength decreased could increase the risk of MCI(OR = 3.008, 95%CI: 1.421,6.369), higher PASE score was correlated with lower risk of MCI (OR = 0.402, 95%CI: 0.168,0.966). After combining body composition indices, handgrip strength and PASE score remained significantly associated with the occurrence of MCI, and there is an interaction. Logistic regression models were used for receiver operating characteristic curve analysis, all models demonstrate a good level of predictive performance for MCI. Physical activity level and physical function are associated with mild cognitive impairment. Higher physical activity level, normal handgrip strength are correlated with lower risk of MCI.